The transformation of the German vocational training regime: evidence from firms' training behaviour - Busemeyer, Marius R. [Verfasser]; Neubäumer, Renate [Verfasser]; Pfeifer, Harald [Verfasser]; Wenzelmann, Felix [Verfasser] (My University, 2012)
"The German system of industrial relations has undergone significant changes in the last decade. This article reflects on and provides empirical evidence for how these changes have affected the training behaviour of firms. Conventional perspectives would predict a general decline in training investment when the constraints of collective wage bargaining are loosened. Relying on a large data set on the costs and benefits of apprenticeship training for the years 2000 and 2007, we do find evidence for this hypothesis but would add that the strength of the effect varies strongly across different types of firms. Large firms have benefited much more from participating in training than have small firms and have therefore maintained their investment in training because they are able to reduce net costs by expanding the productive contributions of apprentices. This finding may help to explain the apparent resilience of the German training system in the recent economic and financial crisis." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 3.2 Unternehmen und Behörden; S 4.1 Finanzierungsquellen; S 2.1.6 Arbeits- & Tarifrecht; Ausbildungsbereitschaft; Ausbildungsverhalten; Ausbildungsinvestition; Einflussfaktor; Tarifvertrag; Betriebsgröße; Empirische Untersuchung